CRISPR/Cas9-engineering of Kell null erythrocytes to unveil host targeted irresistible antimalarial - Geeta Kumari; Pragya Gupta; Sangam G. Goswami; Ravi Jain; Sakshi Anand; Shreeja Biswas; Swati Garg; Priya Thakur; Vinodh Saravanakumar; V. R. Arvinden; Bidhan Goswami; Ipsita Pal Bhowmick; et al. (Communications Biology)
Abstract Malaria elimination faces challenges from drug resistance, stemming from mutations within the parasite’s genetic makeup. Genetic adaptations in key erythrocyte proteins offer malaria protection in endemic regions. Emulating nature’s approach, and implementing methodologies to render indispensable host proteins inactive, holds the potential to reshape antimalarial therapy. This study delves into the functional implication of the single-span membrane protein Kell ectodomain, which shares consensus sequence with the zinc endopeptidase family, possesses extracellular enzyme activity crucial for parasite invasion into host erythrocytes. Through generating Kell-null erythrocytes from an erythroid progenitor, BEL-A, we demonstrate the indispensable nature of Kell activity in P. falciparum invasion. Additionally, thiorphan, a metallo-endopeptidase inhibitor, which specifically inhibits Kell activity, inhibited Plasmodium infection at nanomolar concentrations. Interestingly, individuals in malaria-endemic regions exhibit low Kell expression and activity, indicating a plausible Plasmodium-induced evolutionary pressure. Both thiorphan and its prodrug racecadotril, demonstrated potent antimalarial activity in vivo, highlighting Kell’s protease role in invasion and proposing thiorphan as a promising host-oriented antimalarial therapeutic.